2017
DOI: 10.1103/physreva.95.052504
|View full text |Cite
|
Sign up to set email alerts
|

Combining Slater-type orbitals and effective core potentials

Abstract: We present a general methodology to evaluate matrix elements of the effective core potentials (ECPs) within one-electron basis set of Slater-type orbitals (STOs). The scheme is based on translation of individual STO distributions in the framework of Barnett-Coulson method. We discuss different types of integrals which naturally appear and reduce them to few basic quantities which can be calculated recursively or purely numerically. Additionally, we consider evaluation of the STOs matrix elements involving the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 174 publications
(209 reference statements)
0
9
0
Order By: Relevance
“…Our final theoretical value of the static polarizability α 0 = 2.66080 (36) has an estimated uncertainty of about one part per 10 4 . The most recent experimental value for this quantity, α 0 = 2.661057 (7), obtained by Gaiser and a after applying the correction for the compressibility Fellmuth [7], lies within our error bars, but is about 50 times more accurate.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Our final theoretical value of the static polarizability α 0 = 2.66080 (36) has an estimated uncertainty of about one part per 10 4 . The most recent experimental value for this quantity, α 0 = 2.661057 (7), obtained by Gaiser and a after applying the correction for the compressibility Fellmuth [7], lies within our error bars, but is about 50 times more accurate.…”
Section: Discussionmentioning
confidence: 88%
“…These bases, optimized using the methodology established in Refs. [35,36], are available from authors upon request. Computer codes for the STO integrals, described in Refs.…”
Section: A Clamped-nucleus Nonrelativistic Polarizabilitymentioning
confidence: 99%
“…[55] For the Ca, Sr, and Ba atoms we used the STO basis sets specifically designed for the calculations with the effective core potentials. [56] The following Gaussian basis sets were used: for Ca the ECP10MDF pseudopotential [57] together with the [12s12p6d] basis augmented with a set of [1s1p1d] diffuse functions, for Sr [8s8p5d4f 1g] augmented with a set of [1s1p1d1f 3g] diffuse functions [58] and the ECP28MDF pseudopotential, [57,59,60] for Ba the ECP46MDF pseudopotential [57] together with the [9s9p6d4f 2g] Gaussian basis set. [57] To assess the quality of the basis sets, in Tables 2 -4 we present the excitation energies obtained with the EOM-CCSD and EOM-CC3 codes and compare them with the experimental results.…”
Section: Basis Setsmentioning
confidence: 99%
“…However, there are significant discrepancies for the 1 D and 3 D states. Within the Gaussian basis set both EOM-CCSD and EOM-CC3 iterations did not converge to the desired states, and within the Slater basis set the [56] revealed that this is an inherent problem of the pseudopotentials used in the calculations. The authors of Ref.…”
Section: Basis Setsmentioning
confidence: 99%
See 1 more Smart Citation